Sero prevalence of virus-neutralizing antibodies for rabies in street dogs of Kathmandu Valley, Nepal - Shikha Rimal (2020)
© 2019 Rimal et al. Introduction: Rabies is a vaccine-preventable viral zoonotic disease that remains a serious global public health concern. Rabies vaccination with adequate coverage of the canine population has been shown to control rabies outbreaks among canines and to prevent the transmission of rabies from dogs to humans. As vaccination is the primary control measure for rabies, it is important to determine the level of anti-rabies antibodies in animals in order to determine the effectiveness of the control measures being implemented. Materials & Methods: Blood samples were collected from 50 street dogs (August 2016 to December 2016) in Kathmandu, Bhaktapur and Lalitpur districts. Rabies sero-conversion on the separated serum was quantified using PlateliaTM Rabies II Kit (Bio-Rad, China) according to the manufacturer’s recommendations. Results: Eighty percent (40/50) of the serum samples surpassed the requested level of rabies antibodies, suggesting good coverage of vaccination among street dogs. Conclusion: However, an active dog surveillance system with a dog registration process before and after vaccination campaigns, and a multi-dimensional approach including all stakeholders, are necessary to eradicate rabies from the canine population in Nepal.